Implementation of Accreditation Policies for Early Childhood, Primary, and Secondary Education to Improve Education Quality in South Sumatra - Aryanisila Aryanisila; Achmad Ridhuan Habena; Sunarto Sunarto (GAYAKU PUBLISHER, 2026)
Background: Accreditation is an external evaluation conducted by the National Accreditation Board for Early Childhood Education, Elementary and Secondary Education (BAN-PDM), which serves as an important instrument for educational quality assurance to assess the suitability of educational units based on national education standards. In its implementation in South Sumatra, various obstacles are still found, including limited infrastructure, the quality of human resources (educators and education personnel), as well as quality disparities between regions considering that South Sumatra has diverse geographical areas including lowlands, swamps, coasts, and mountains. Objective : This study aims to analyze the implementation of accreditation policies for Early Childhood Education, Elementary and Secondary Education in improving the quality of education in South Sumatra. Research Method : This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through interviews, observations, and documentation of related parties, such as Members of BAN PDM South Sumatra, Education Offices, Assessors, Principals, Teachers, Education Personnel, and the community around the area of schools visited. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. Results: The results of the study indicate that schools that are well accredited tend to have a more effective governance system. Conclusion : The implementation of accreditation policies can be said to have a positive contribution to improving the quality of education. However, it still requires improvements in the aspects of equity, mentoring, and resource support so that the goal can be achieved optimally.